Musical Practice as a Space of Children’s Social Inclusion: Experiences of Portal Norteño Music Perú in Huacho, Huara - Salas Rivera, Isabel Lucía (2018)
The aim of the present article is to demonstrate the role of musical practice in the social transformation of children and youth in the city of Huacho, with a central focus on the project Portal Norteño Music Perú in the lives of these children, their families, and society. Due to the absence of publications on this topic in Peru, there is a lack of adequate prior information; for this reason, this research has been exploratory in nature. The collection of data and the picture of the current state were achieved through a methodology of direct observation; description; interviews with children in the chorus and orchestra; and conversations with the mothers, music instructors, municipal authorities of Huacho, and with the founder and director of the project. In the present work, we address how the project has had an important effect and how the efforts oriented to improving the lives of these children have been satisfactory. We conclude considering what is necessary to extend the actions of this form of musical practice to contexts of greater social risk and vulnerability.